The Effect of Digitalization in the Workplace on Employee Performance Mediated By Employee Attachment (Study on Employees of the Center for Product Processing Research and Marine and Fisheries Biotechnology, Central Jakarta) - Indrihastuti Sulistianingtiyas; Indi Djastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digitization in the workplace based on technology activities is leading to new ways of working that organizations need. In a digital work environment, individual work styles have an effect on overall efficiency and performance. The implementation of digitization in the workplace was introduced as a performance improvement, but the complexity of learning requires extra time and willingness of employees to learn new technologies. The purpose of this study was to examine and analyze the effect of digitization in the workplace on employee performance mediated by employee engagement. The population in this study was ASN BBRP2BKP with a total of 92 people. This study uses a survey method for collecting descriptive quantitative data with questionnaires and census techniques on all members of the population. The analysis technique uses Partial Least Squares (PLS). The results of this study indicate that digitization in the workplace has a positive and significant effect on employee performance which is mediated by employee engagement. The managerial implication of this research is that digitization in the workplace increases employee performance expectations thereby increasing work productivity, fostering good employee attitudes towards the use of technology, increasing employee self-efficacy in completing work, encouraging employees to take initiative, updating skills, creative solutions, active participation, new challenges, as well as enabling employee engagement in an integrated and sustainable way of thinking with passion and determination to work with dedication in doing work seriously.